Descriptive Study: Workload Analysis of Regional X Hospital Employees Experiencing Career Mismatch - Ni Kadek Meliani; I Gde Dhika Widarnandana; Lidtiyani Dewi Hartika, M.Psi., (LPPM Universitas Dhyana Pura, 2025)
This study aims to find out how the workload experienced by employees who experience career mismatch at RSUD X, where there are 135 employees who experience career mismatch. The data obtained in this study is the result of distributing questionnaires to 114 samples from a total of 135 existing populations. The results of distributing the questionnaires were tested for validity and reliability to ensure that the instrument in the form of a questionnaire used was valid and reliable. Based on the results of the analysis conducted, it is known that workload indicators that affect employees who experience mismatched careers are in terms of office facilities, as well as handling violations that occur in the workplace. Whereas other things in the workload indicator in the form of physical demands, mental demands, time demands, training efforts, SOP implementation, and work knowledge do not put pressure in the form of workload on employees who experience career mismatches at RSUD X.